EDUCATION LEVEL, AGE, CAESAREAN SECTION SURGERY HISTORY, AND RECOVERY DURATION IN POST-OPERATIVE CAESAREAN SECTION PATIENTS - Putra, Kusuma Wijaya Ridi; Riesmiyatiningdyah, Riesmiyatiningdyah; Listari, Risti Puji; Diana, Meli; Toonsiri, Chanandchidadussadee (Nurse and Holistic Care, 2022)
Abstract Background: Caesarean section surgery is a delivery procedure performed for mothers who want to give birth with complications. The recovery process from caesarean section surgery will vary from one person to another. Several factors can affect the recovery duration of caesarean section surgery, including education level, age, history of caesarean section surgery, motivation given by health workers, early mobilization provided by health workers, and others. Objective: This study aimed to analyse the relationship between education level, age, history of caesarean section surgery, and recovery duration of post-operative caesarean section surgery. Methods: The research design used is descriptive-analytic research with a cross-sectional approach. This research was carried out from May 5, 2021, until June 15, 2021, in the Recovery Room of the General Hospital of Jasem, Sidoarjo. The sampling technique used is incidental sampling, so the number of respondents obtained in this study is 50. The research instrument used was medical records to determine the level of education, age and history of caesarean section surgery. In addition, the researchers also used the Bromage Scale to evaluate the duration of recovery from post-operative caesarean section surgery. The statistical test used was the Spearmen Rho test with a significance level of < .05 using SPSS 21. Results: This study showed a relationship between age and history of caesarean section surgery (p-value < .05, r = .310). The results of this study also showed that there was a relationship between age and history of caesarean section surgery with duration of recovery of post-operative caesarean section surgery (p-value < .05, r = .356; p-value < .001, r = .603, respectively). Conclusion: This study found that health workers are expected to consider age and history of caesarean section surgery in the recovery process of post-operative caesarean section surgery patients.